Statin pretreatment is associated with better outcomes in large artery atherosclerotic stroke - Tsivgoulis, Georgios; Katsanos, Aristeidis H; Sharma, Vijay K; Krogias, Christos; Mikulik, Robert; Vadikolias, Konstantinos; Mijajlovic, Milija; Safouris, Apostolos; Zompola, Christina; Faissner, Simon; Weiss, Viktor; Giannopoulos, Sotirios; et al. (Neurology, 2016)
OBJECTIVE: Even though statin pretreatment is associated with better functional outcomes and lower risk of mortality in acute ischemic stroke, there are limited data evaluating this association in acute ischemic stroke due to large artery atherosclerosis (LAA), which carries the highest risk of early stroke recurrence. METHODS: Consecutive patients with acute LAA were prospectively evaluated from 7 tertiary-care stroke centers during a 3-year period. Statin pretreatment, demographics, vascular risk factors, and admission and discharge stroke severity were recorded. The outcome events of interest were neurologic improvement during hospitalization (quantified as the relative decrease in NIH Stroke Scale score at discharge in comparison to hospital admission), favorable functional outcome (FFO) (defined as modified Rankin Scale score of 0-1), recurrent stroke, and death at 1 month. Statistical analyses were performed using univariable and multivariable Cox regression models adjusting for potential confounders. All analyses were repeated following propensity score matching. RESULTS: Statin pretreatment was documented in 192 (37.2%) of 516 consecutive patients with LAA (mean age: 65 ± 13 years; 60.8% men; median NIH Stroke Scale score: 9 points, interquartile range: 5-18). Statin pretreatment was associated with greater neurologic improvement during hospitalization and higher rates of 30-day FFO in unmatched and matched (odds ratio for FFO: 2.44; 95% confidence interval [CI]: 1.07-5.53) analyses. It was also related to lower risk of 1-month mortality and stroke recurrence in unmatched and matched analyses (hazard ratio for recurrent stroke: 0.11, 95% CI: 0.02-0.46; hazard ratio for death: 0.24, 95% CI: 0.08-0.75). CONCLUSION: Statin pretreatment in patients with acute LAA appears to be associated with better early outcomes regarding neurologic improvement, disability, survival, and stroke recurrence.
Keywords: senioři; intrakraniální arterioskleróza; Stroke; lidé; Middle Aged; mužské pohlaví; míra přežití; Prospective Studies; cévní mozková příhoda; Follow-Up Studies; Hydroxymethylglutaryl-CoA Reductase Inhibitors; následné studie; ženské pohlaví; Humans; prospektivní studie; statiny; Survival Rate; lidé středního věku; Hospitalization; hospitalizace; Female; Aged; Intracranial Arteriosclerosis; Male